2015
DOI: 10.1111/joa.12396
|View full text |Cite
|
Sign up to set email alerts
|

The ear region of earliest known elephant relatives: new light on the ancestral morphotype of proboscideans and afrotherians

Abstract: One of the last major clades of placental mammals recognized was the Afrotheria, which comprises all main endemic African mammals. This group includes the ungulate-like paenungulates, and among them the elephant order Proboscidea. Among afrotherians, the petrosal anatomy remains especially poorly known in Proboscidea. We provide here the first comparative CT scan study of the ear region of the two earliest known proboscideans (and paenungulates), Eritherium and Phosphatherium, from the mid Palaeocene and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Ma, which is younger than the minimum age for the oldest stem proboscidean (Eritherium, 59.2 Ma) (Gheerbrant, 2009;Schmitt and Gheerbrant, 2016;Kocsis et al, 2014 Fox et al, 2010). Thus, Phillips' (2016) estimated divergence times for four superordinal clades in Laurasiatheria (Ostentoria, Zoomata, Fereuungulata, Variamana) are all younger than the oldest stem fossils for Carnivora (Fox et al, 2010).…”
Section: Inspection Ofmentioning
confidence: 99%
“…Ma, which is younger than the minimum age for the oldest stem proboscidean (Eritherium, 59.2 Ma) (Gheerbrant, 2009;Schmitt and Gheerbrant, 2016;Kocsis et al, 2014 Fox et al, 2010). Thus, Phillips' (2016) estimated divergence times for four superordinal clades in Laurasiatheria (Ostentoria, Zoomata, Fereuungulata, Variamana) are all younger than the oldest stem fossils for Carnivora (Fox et al, 2010).…”
Section: Inspection Ofmentioning
confidence: 99%
“…The first studies concern extant elephants, and they date back to as early as 1710 conducted by Blair (1710). Comparisons were made with the published data on two Eocene taxa Moeritherium (Court, 1994) and Numidotherium koholense (Court, 1992;Benoit et al, 2013b;Schmitt and Gheerbrant, 2016), the Pleistocene Elephantimorpha from Friesenhahn Cave (Ekdale, 2011) and extant elephants Elephas and Loxodonta (Spoor et al, 2007;Manoussaki et al, 2008;Ekdale, 2011;Benoit et al, 2013aBenoit et al, , 2013b. The present paper increases the knowledge on Proboscidean petrosal morphology by describing specimens of an endemic taxa.…”
Section: Discussionmentioning
confidence: 80%
“…The present study concerns three petrosal bones of the dwarf elephants, Palaeoloxodon tiliensis that lived on Tilos Island in Greece during the Late Quaternary (Theodorou et al, 2007). Since there is little information on the morphology of the ear region of proboscideans (Blair, 1710;Court, 1992Court, , 1994Ekdale and Rowe, 2011;Benoit et al, 2013aBenoit et al, , 2013bEkdale, 2013;Schmitt and Gheerbrant, 2016) and none of insular endemic species, this study will contribute to the available knowledge on Proboscidean inner ears. The work presented here will also contribute to our understanding of insular evolution and is part of a series of various research papers on proboscideans, providing comparison of their inner ears and commenting on their agility.…”
Section: Introductionmentioning
confidence: 99%
“…given by Ekdale, who found that this golden mole had the ancestral placental condition. A secondary common crus is lacking in extant Tenrecidae and Macroscelidea but it was present in the supposed elephant‐shrew Chambius from the early‐mid Eocene (Benoit, Orliac, et al, ), as well as other afrotherians including Orycteropus (Ekdale, ), an unnamed stem sirenian (Benoit, Orliac, et al, ), and the stem proboscidians Numidotherium and Phosphatherium (Benoit, Merigeaud, & Tabuce, 2013; Schmitt & Gheerbrant, ). It seems possible that the presence of a secondary common crus in chrysochlorids is a retained characteristic, plesiomorphic for Afrotheria as a whole but secondarily lost in many extant groups.…”
Section: Discussionmentioning
confidence: 99%
“…A discrete canaliculus cochleae is lacking in extant elephants and sirenians, in which the perilymphatic duct and round window are confluent (Ekdale, ; Fischer, ; Fleischer, ). Fossil evidence suggests that this condition was acquired convergently (Court & Jaeger, ; Schmitt & Gheerbrant, ). A similar morphology has been described in the extinct embrithopod Arsinoitherium (Court, ), also an afrotherian, some pinnipeds (Wyss, ) and the grey whale Eschrichtius (Ekdale, Berta, & Deméré, ; Geisler & Luo, ).…”
Section: Discussionmentioning
confidence: 99%